Maternal outcome following uterine rupture and its associated factors among mothers who delivered at Felege-Hiwot referral hospital, Amhara-Ethiopia - Wesson, Alemtsehay; Assefa, Enyew (International Journal of Scientific Reports, 2018)
Background: Ruptured uterus is one of the major causes of maternal and prenatal morbidities and mortalities in developing countries, particularly in Africa. Ethiopia is one of developing countries where maternal and prenatal mortalities are still high. The major objective of this study was to determine maternal outcomes of uterine rupture and its associated factors. Methods: The study design was facility based retrospective cross-sectional study from all mothers who visit from 01 September 2011 to 31 August 2015 at Felege-Hiwot referral hospital delivery room for delivery service with ruptured uterus was conducted in the study. A total of 312 cases were enrolled in the study. The table, graph and binary logistic regression was found to be more appropriate for analyzing the data. Results: More than 39% mothers had severe complication. The common complication was severe anemia 24.4% followed by severe shock 14.7%. There were also 2.7% maternal deaths. The binary logistic regression model showed that incidence and its complication of uterine rupture in this study were remarkably high. Antenatal care visit, duration of labor and admission to laparotomy time and hospital stay had strong association with maternal outcome. Conclusions: Improving access to antenatal care, proper monitoring of labor and early referral of high risk patients will contribute to the reduction of unfavorable maternal outcome.